2022
DOI: 10.1177/14649934221080828
|View full text |Cite
|
Sign up to set email alerts
|

‘Making Strange’: Discourse Analysis Tools for Teaching Critical Development Studies

Abstract: Critical development studies require not just a critical attitude, but also usable tools. This article suggests some forms of discourse analysis that can add substance to critical development studies’ aspirations and that can yet be learnt and used by students without specialist background. Central are tools for ‘making strange’ (defamiliarization), so that we view both texts and social realities in a fresh independent way and start to discern better their blindspots, and our own. The article presents accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Several studies conducted across contexts also found that care-seeking individuals lack adequate knowledge and awareness on patient rights. These studies, like ours demonstrated that care-seeking individuals relied upon the health care professionals to know about patient rights [45][46][47][48][49]. Even if care-seeking individuals and their families had knowledge about patient rights, most often they preferred not to claim their rights partly owing to the fear of reprisal from care-providers.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several studies conducted across contexts also found that care-seeking individuals lack adequate knowledge and awareness on patient rights. These studies, like ours demonstrated that care-seeking individuals relied upon the health care professionals to know about patient rights [45][46][47][48][49]. Even if care-seeking individuals and their families had knowledge about patient rights, most often they preferred not to claim their rights partly owing to the fear of reprisal from care-providers.…”
Section: Discussionmentioning
confidence: 74%
“…Critical theorists such as Fairclough (2015) [42] & Van Dijk (1988) [43] contend that a critical analysis of language provides deeper insights into ideas, practices and power relations that are often not explicit. Furthermore, Gasper (2022) [45] argues that the purpose of CDA is to challenge the power structures that embody "systems of social exclusion and injustices in the linguistic systems". Van Dijk (2017) [46] indicates that by examining the choice of words, sequences, patterns, omissions, additions, metaphors, euphemisms, conspicuous, inconspicuous communicative actions, utterances, silences, and expressions, we will be able to understand how socialpolitical practices (on patient rights) are discursively constructed.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques may help in resisting temptations to buy into some social constructions of target populations in nudging some target populations more than others Howlett 2018). More research is needed to understand such skill sets and mindsets and how to foster them (see Gasper 2022).…”
Section: Summary and Ways Forward 81 Lessons Learnedmentioning
confidence: 99%